AB0802 Osteoporosis in systemic sclerosis: case-control study with a french ofely cohort and risk factors. (12th June 2018) - Thietart, S.; Gatfosse, M.; Sornay-Rendu, E.; Lemeunier, L.; Delmaire, P.; Sellam, J.; Berenbaum, F.; Fain, O.; Chapurlat, R.; Mekinian, A.
Abstract : Background: Systemic sclerosis (SSc) is a rare autoimmune disorder characterised by a vascular and fibrosing involvement of the skin and internal organs. Data about the association between systemic sclerosis (SSc) and osteoporosis (OP) are controversial and scarce about the risk factors of OP in SSc. 1, 2 Objectives: The aim of the study was to determine the OP frequency in SSc and assess its risk factors. Methods: In a prospective cohort of SSc patients, usual risk factors of OP were assessed, as well as SSc organ involvements: pulmonary, cardiac, skin and renal involvements and SSc treatments. All patients underwent dual energy X-ray absorptiometry: bone mineral density (BMD) was measured at the lumbar spine (LS), femoral neck (FN) and total hip (TH). Osteoporosis was defined as having a T-score inferior to −2.5. Results: Forty-eight patients were included with a median age of 60 years, 27–81 41 women (85.4%), with a diffuse cutaneous subtype in 13 cases (27.1%) and illness duration of 12.6 years (0.3–41.1). Average BMD was 0.98±0.21 in LS, 0.84±0.13 in FN and 0.86±0.15 in TH. OP was found in 19 patients (40%). Among patients with OP, an associated auto-immune disorder was found in 13 patients (68.4%) versus 10 (34.5%) in the non-OP group (p=0.04), digestive sub-occlusion in 4 patients (21% versus 0 patients, p=0.02), and chronic liver disease in 6 patients (31.6%) versus 2 (6.9%, p=0.04). Respiratory explorations found a DLCO of 12.7 (6.8–17.2) versus 15.6 (9.6–32.2) (p=0.007), a CVF of 2.47 (1.1–4) versus 3 (1.7–5.9) (p=0.03). DAS28-CRP was significantly higher (2.29 (1, 53–4.46) in the OP group versus 1.86 (0–3.8) in the non-OP group, p=0.02); with a higher frequency of hand X-ray erosions (6 OP patients (31.6%) versus 2 (6.9%), p=0.04). No difference was found in Rodnan score, SSc subtype, illness duration, malnutrition, treatments (proton pump inhibitors, cyclophosphamide, steroids), autoantibodies profile; nor with the usual OP risk factors: age, smoking, personal or family history of OP fractures, alcohol consumption, weight, BMI, long term steroid treatment, early menopause and thyroid disease. No difference in serum vitamin D, calcium, thyroid hormones and C-reactive protein levels was found between OP and non-OP groups. Conclusions: Osteoporosis was associated with SSc-related factors such as: articular, digestive and respiratory involvements, and associated auto-immune diseases. Usual OP risk factors where not significantly different between osteoporotic SSc patients and non-osteoporotic patients. References: [1] Caimmi C, Caramaschi P, Barausse G, Orsolini G, Idolazzi L, Gatti D, et al. Bone Metabolism in a Large Cohort of Patients with Systemic Sclerosis. Calcif Tissue Int. 2016Jul 1;99(1):23–9. [2] Omair MA, Pagnoux C, McDonald-Blumer H, Johnson SR. Low bone density in systemic sclerosis. A systematic review. J Rheumatol. 2013Nov;40(11):1881–90. Disclosure of Interest: None declared